Fundamentals of entreprneurship (ENT300) : Haci Sdn Bhd / Immanuel David ... [et al.]. - David, Immanuel; Azaman, Mohd. Amiruddin; Tuah, Hasif Aiman; Chundang, Cliff Howell (2017)
HACI is the new print brokerage firm formed as sole proprietorship. We will offer printing service for a wide range of print media. Our goal is to serve the printing needs for our company to be a one-stop-shop. While our services, quality , and prices will be far affordable for our customer so that we can build long-term relationships with our customers. Our customers mainly are students because our company are located inside of the campus. Not only that our location is strategic, it also will help our company to become much more recognizes as the students are truly in need for printing services to finish their assignments. However, there are advantages and disadvantages if we are to be to run this company.